2023
DOI: 10.1021/acs.bioconjchem.3c00080
|View full text |Cite
|
Sign up to set email alerts
|

First Comparison Study of the In Vitro and In Vivo Properties of a Randomly and Site-Specifically Conjugated SPECT/NIRF Monomolecular Multimodal Imaging Probe (MOMIP) Based on an aza-BODIPY Fluorophore

Abstract: Among all approaches in molecular imaging, the combination of near-infrared fluorescence imaging (NIRF) with radioisotopic imaging (PET or SPECT) allows one to benefit from the advantages of each of the imaging techniques, which are very complementary and of comparable sensitivity. To this end, the construction of monomolecular multimodal probes (MOMIP) has made it possible to combine the two imaging modalities within the same molecule, thus limiting the number of bioconjugation sites and yielding more homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In order to compare the two bioconjugation strategies, the Wazaby-DOTA probe was functionalized either with an ethyl-squaramate linker for random bioconjugation or with a DBCO linker for site-specific bioconjugation (Figures 1 and 2A). 34 Bioconjugations were performed in carbonate bicarbonate buffer (pH = 8.9) with 3 equiv of probe per antibody. The random bioconjugation conditions were optimized to get a DOL (degree of labeling) between 1.5 and 2, comparable to the one usually obtained thanks to the site-specific approach.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to compare the two bioconjugation strategies, the Wazaby-DOTA probe was functionalized either with an ethyl-squaramate linker for random bioconjugation or with a DBCO linker for site-specific bioconjugation (Figures 1 and 2A). 34 Bioconjugations were performed in carbonate bicarbonate buffer (pH = 8.9) with 3 equiv of probe per antibody. The random bioconjugation conditions were optimized to get a DOL (degree of labeling) between 1.5 and 2, comparable to the one usually obtained thanks to the site-specific approach.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to compare the two bioconjugation strategies, the Wazaby-DOTA probe was functionalized either with an ethyl-squaramate linker for random bioconjugation or with a DBCO linker for site-specific bioconjugation (Figures and A) …”
Section: Resultsmentioning
confidence: 99%
“…The advantage of a site-specific conjugation in regard to random conjugation has been clearly proven . In particular, for optical imaging using aza-BODIPY fluorophores, we previously observed that an improved in vivo behavior of the conjugates was reported when the fluorophore was grafted site-specifically to the biovector. , Therefore, it was crucial for us to conjugate the fluorophores in a site-specific manner.…”
Section: Resultsmentioning
confidence: 99%
“…trans -Cyclooctene (TCO)/tetrazine ligation has been extensively studied, and we decided to functionalize the antibodies with TCO moieties in a site-specific way. Indeed, the superiority of site-specific conjugation vs random conjugation on lysine residues has been well established, leading to much more chemically defined and homogeneous conjugates. , Among the existing site-specific conjugation methods, we have chosen the efficient enzymatic ligation of amine derivatives on the heavy chain of IgGs catalyzed by transglutaminase (MTGase) (Scheme ). , Besides being affordable, this technique requires removal of the glycan chains located in positions N297, which could help reducing off-target uptake in the liver and spleen, thanks to an impaired FcγRI binding. , This feature might be interesting as fluorophores have a tendency to increase the liver uptake due to their hydrophobicity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Bimodal imaging, combining a preoperative imaging technique and real-time fluorescence imaging is an attractive solution to increase the extent of tumor resection. , Indeed, nuclear medicine imagingeither single-photon emission computed tomography (SPECT) or PETcan be used to detect tumors and select patients eligible for FGS. Several strategies can be employed for the synthesis of such bimodal bioconjugates. , Random and sequential introduction of the two probes leads to a highly heterogeneous mixture of millions of conjugates with different numbers of probes per antibody, various ratios of the two probes, and a multitude of possible locations of these probes on the protein. This may have deleterious consequences, including a poorly reproducible synthesis, a potential effect on the photophysical properties of the dye, and, more importantly, different pharmacokinetics and in vivo fate of the different bioconjugates, or even a loss of affinity of the antibodies for their target. For these reasons, we focused on a more elegant strategy involving the following: (i) the preparation of a so-called monomolecular multimodal imaging probe (MOMIP) bringing together the dye and the chelator on a tetrazine platform and (ii) the click conjugation of this MOMIP on the antibodies, previously modified site-specifically with a trans -cyclooctene (TCO) group, through an inverse-electron-demand Diels–Alder (iEDDA) reaction. In this study, we wish to report the synthesis of two dually functionalized immunoconjugatescontaining both a near-infrared (NIR) fluorophore (IRDye800CW) for FGS and desferrioxamine (DFO), the standard chelating agent so far for 89 Zr-labeling of antibodiesand the in vitro validation of their ability to bind ET receptors on CHO-ET A and CHO-ET B cells.…”
Section: Introductionmentioning
confidence: 99%